Temporal and spatial changes and equity of nursing human resources configuration in Sichuan province, China - Yang, Huan; Song, Yayun (Acta Bioethica, 2024)
This research aims to analyze the configuration, distribution, and equity of nursing human resources in Sichuan Province, China, providing a reference for the future development of nursing care in the region. A descriptive analysis was conducted to describe the configuration of nursing human resources in 2010, 2015, and 2020. The Lorenz curve, Gini coefficient, health resource density index, and distribution density maps were used as resources and methodology to evaluate the changes and equity in the configuration of nursing human resources. The result of this research determined that the nurse-to-population ratio was 1.17, 2.09, and 3.42 in 2010, 2015, and 2020, and nursing staff accounted for 24%, 49%, and 35% of technical health personnel. The nurse-to-physician ratio was 1:0.72, 1:1.05, and 1:1.22 in the three years. The Gini coefficients of nursing resource allocation for permanent population and area were 0.24, 0.20, and 0.12 and 0.74, 0.72, and 0.72, respectively. The nursing resource density index was 0.50, 0.91, and 1.42, respectively. In conclusion, the study shows that the equity of nursing resources based on population increased, while the equity based on region still showed disparity, with a sustained increase in nursing human resource density from 2010 to 2020. However, it is necessary to continue increasing the number of nurses and improving the geographical accessibility of nursing care.